Factors Caribbean Overseas Students Perceive Influence their Academic Self-Efficacy - Edwards-Joseph, Arline; Baker, Stanley (Journal of International Students, 2014)
This study investigated factors that influenced the academic self-efficacy of Caribbean overseas students attending universities in the United States, and the themes that emerged from their perceptions of variables impacting their academic self-efficacy. Seven major themes (educational background, faith in God, finances, age and maturity, influence and support of others, selfdetermination, and previous success of other and of self) emerged as factors that influenced the students’ academic self-efficacy. Recommendations for counselors and areas for future research are discussed.